COMMUNICATION IN TIMES OF PANDEMIC, IMPACT IN ECUADORIAN EDUCATION - Vallejo, Msc. Alida; PALACIOS, OSWALDO ZAVALA; TERAN, CESAR NOBOA; AMAYA, JOSEFINA RAMIREZ; ROJAS, ANA MARIA VITERI (International Journal of Research -GRANTHAALAYAH, 2020)
Currently, the COVID 19 pandemic has changed the world and all systems of society, bringing new demands on education and care in public service entities and the work of millions of people in the world. The new digital technologies have allowed the world to function in some way in this period of time, in all areas of society. In education a constant interaction is needed, between teachers and students, during teaching - learning. However, there are factors that affect this process, including internet accessibility, digital literacy, and the economic capacity of families to acquire an electronic device. In this sense, the Ecuadorian government must take actions to guarantee that students have access to the demands of the 21st century. The objective of this article is to analyze how the population is adapting to the new educational scheme, to visualize the urgent needs and give suggestions to solve them.